Impact of early palliative care on caregivers of patients with advanced cancer: cluster randomised trial. (29th September 2016) - McDonald, J.; Swami, N.; Hannon, B.; Lo, C.; Pope, A.; Oza, A.; Leighl, N.; Krzyzanowska, M. K.; Rodin, G.; Le, L. W.; Zimmermann, C.
Abstract: Background: Early palliative care improves the quality of life (QoL) and satisfaction with care of patients with advanced cancer, but little is known about its effect on caregivers. Here, we report outcomes of caregiver satisfaction with care and QoL from a trial of early palliative care. Patients and methods: Twenty-four medical oncology clinics were cluster-randomised, stratified by tumour site (lung, gastrointestinal, genitourinary, breast and gynaecological), to early palliative care team referral, or to standard oncology care with palliative care only as needed. Caregivers of patients with advanced cancer (clinical prognosis of 6–24 months, Eastern Cooperative Oncology Group 0–2) in both trial arms completed validated measures assessing satisfaction with care (FAMCARE-19) and QoL [SF-36v2 Health Survey; Caregiver QoL-Cancer (CQoL-C)], at baseline and monthly for 4 months. We used a multilevel linear random-intercept mixed-effect model to test whether there was improvement in the intervention group relative to the control group over 3 and 4 months. Results: A total of 182 caregivers completed baseline measures (94 intervention, 88 control); 151 caregivers (77 intervention, 74 control) completed at least one follow-up assessment. Satisfaction with care improved in the palliative intervention group compared with controls over 3 months ( P = 0.007) and 4 months ( P = 0.02). There was no significant improvement in the intervention group compared with controls for CQoL-C (3 months: P = 0.92, 4 months: P = 0.51), Physical Component Summary of the SF-36v2 Health Survey (3 months: P = 0.83, 4 months: P = 0.20), or Mental Component Summary of the SF-36v2 Health Survey (3 months: P = 0.87, 4 months: P = 0.60). Conclusion: Early palliative care increased satisfaction with care in caregivers of patients with advanced cancer. ClinicalTrials.gov identifier: NCT01248624.